1995
DOI: 10.1111/j.1365-2133.1995.tb06933.x
|View full text |Cite
|
Sign up to set email alerts
|

Satisfactory remission achieved by PUVA therapy in a case of crisis-type adult T-cell leukaemia/lymphoma with generalized cutaneous leukaemic cell infiltration

Abstract: We used PUVA therapy in a patient with crisis-type adult T-cell leukaemia/lymphoma and generalized cutaneous leukaemic cell infiltration. PUVA proved very effective in reducing leukaemic cells and in clearing the eruption. To understand the way in which PUVA produced a reduction in the number of leukaemic cells, we examined peripheral blood cells by light and electron microscopy. Light microscopy was of little help, but electron microscopy revealed that PUVA induced apoptosis-like changes in circulating leukae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Recently, we have reported that PlNA therapy induces satisfactory remission in a crisis type adult T cell leukemia/lymphoma, suggesting that the treatment might be effective for cases with PlNA-susceptible cells not restricted to the skin (13). In other words, PlNA therapy could be effective in treating more or less systemically-involved cases of T cell malignancy (and activated Langerhans cells) by abrogating epidermotropic skin-associated PlNA-susceptible cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have reported that PlNA therapy induces satisfactory remission in a crisis type adult T cell leukemia/lymphoma, suggesting that the treatment might be effective for cases with PlNA-susceptible cells not restricted to the skin (13). In other words, PlNA therapy could be effective in treating more or less systemically-involved cases of T cell malignancy (and activated Langerhans cells) by abrogating epidermotropic skin-associated PlNA-susceptible cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interferon is apparently more effective for cutaneous lesions than for other lesions. 10,11 Psoralen plus ultraviolet A (PUVA) therapy 12 has been reported by dermatologist to be effective against generalized eruptions. Electron beam irradiation is also effective for a solitary skin nodules.…”
Section: Smoldering and Favorable Chronic Typesmentioning
confidence: 99%
“…In these forms, NB-UVB phototherapy is used for more superficial lesions and PUVA for more infiltrated lesions, with good results. 57,58 A recent study of patients with the smoldering form of ATL and cutaneous involvement demonstrated better survival in those treated with phototherapy combined with etoposide (25 to 75 mg/day for 2 to 4 weeks with a one-week interval or on alternate weeks). 35 As such, the favorable chronic and smoldering types of ATL are considered less aggressive and should be kept under observation until possible progression of the disease, similar to management of chronic lymphocytic leukemia and smoldering myeloma.…”
Section: Treatmentmentioning
confidence: 99%